Electrochemical and Metallurgical Behavior of Lead-Aluminum Casting Alloys as Grids for Lead-Acid Batteries - Khatbi,Salma (2018)
In order to evaluate the influence of aluminum on the corrosion resistance of lead anodes in 4 M H2SO4, as well as on the microcrystalline morphology of lead, different electrochemical and metallurgical studies were made such as potentiodynamic polarization, electrochemical impedance spectroscopy, hardness evolution, X-ray fluorescence spectroscopy and optical microscopy. The obtained results have shown that the addition of aluminum up to 1.5% in weight leads to a significant decrease of the corrosion and passivation rates (Icorr and Ipass) and it reduces the famous sulfation phenomena by facilitating the transformation of PbSO4 and PbO to PbO2. It also makes the micro-structure of Pb much stronger, which makes the Pb anodes more resistant to mechanical shocks within the battery. All of these improvements led to increase the lifetime of the conventional lead-acid battery up to 51.15%. Therefore, the new improved battery is more resistant, durable and more environment friendly.